Perbedaan Perilaku Konsumtif Mahasiswa Ditinjau dari Platform Belanja Online - Laelly Dewi Sekar Tanjung; Mustaqim Setyo Ariyanto; Agus Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine differences in student consumption behavior from online shopping platforms. The method used was a quantitative approach with a comparative study design, the research sample consisted of 107 Yogyakarta students. Data was collected through a questionnaire that measures consumer behavior. Research data was analyzed using the Analysis of Variance (ANOVA) technique. The results of the hypothesis test show that there is no significant difference with a significance value of 0.229. So there is no significant difference in students' consumptive behavior when shopping on the two online shopping platforms tested. Based on these findings, it can be concluded that the two platforms do not influence student consumption behavior differently. This research provides insight that students have consistent consumption patterns even though they shop on different platforms, and suggests developing marketing strategies that are based more on service quality and better user experience rather than platform differences themselves.